2011
DOI: 10.1002/per.806
|View full text |Cite
|
Sign up to set email alerts
|

Why Mate Choices are not as Reciprocal as we Assume: The Role of Personality, Flirting and Physical Attractiveness

Abstract: Based on a social relations perspective on mating, the actual and assumed reciprocity of mate choices was studied in a real-life speed-dating context. A community sample involving 382 singles aged 18-54 years filled out a questionnaire for the measurement of self-perceived mate value, sociosexuality, extraversion, and shyness and participated in free speed-dating sessions. Immediately after each date, choices and assumed choices were recorded. Measures of physical attractiveness and flirting behaviour were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
75
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 64 publications
8
75
2
1
Order By: Relevance
“…A wealth of empirical findings shows that reciprocating romantic attraction influences interpersonal relationships (Back et al, 2011;Greitemeyer, 2010;Peretti & Abplanalp, 2004;Sprecher, 1998;Whitchurch et al, 2011). Because the reciprocation of romantic attraction is desired and expected from potential partners (Back et al, 2011), researchers have sought to explain why playing hard to get (i.e., withholding attraction) is a beneficial dating strategy (Walster et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wealth of empirical findings shows that reciprocating romantic attraction influences interpersonal relationships (Back et al, 2011;Greitemeyer, 2010;Peretti & Abplanalp, 2004;Sprecher, 1998;Whitchurch et al, 2011). Because the reciprocation of romantic attraction is desired and expected from potential partners (Back et al, 2011), researchers have sought to explain why playing hard to get (i.e., withholding attraction) is a beneficial dating strategy (Walster et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Because the reciprocation of romantic attraction is desired and expected from potential partners (Back et al, 2011), researchers have sought to explain why playing hard to get (i.e., withholding attraction) is a beneficial dating strategy (Walster et al, 1973). Brehm's emotion intensity theory, supported by Study 2 results, explain the underlying mechanism regarding reciprocity and attraction.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating another for mate potential, attraction can arise from a range of different attributes such as physical attractiveness, personality, values, and so on [43]. The human perception of attraction is influenced by factors such as media exposure, family pressure, and status.…”
Section: Attractionmentioning
confidence: 99%
“…With the use of visual perception, sexual selection can occur; a natural selection of one human over another, based on preferences of certain characteristics [44,45]. This selection for a potential mate is an important social decision that people make and is a prerequisite for further involvement [43].…”
Section: Attractionmentioning
confidence: 99%
“…We know of only three studies that included investigations of the Matching Hypothesis for global mate value in reallife dating situations, and these studies yielded mixed evidence. Whereas Todd et al (2007) did not find evidence that matching on mate value increased participants' likelihood of choosing a potential partner in a speed-dating situation, Back, Penke, et al (2011) found that participants of a speed-dating event were more likely to flirt with each other if they were more closely matched on mate value. In addition, Taylor et al (2011, Study 4) showed that users of an online dating platform were more likely to communicate with opposite-sex users who had a similar mate value to their own.…”
mentioning
confidence: 93%